2020
DOI: 10.1111/exd.14129
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the significance of cytokines and chemokines in the pathogenesis of alopecia areata

Abstract: Alopecia areata has basically been understood as a type 1 inflammatory disease. Activated NKG2D+CD8+ cells produce the Th1 cytokine interferon‐γ, which leads to the disruption of immune tolerance of hair follicles and the exposure of self‐antigens. This results in dense inflammatory cell infiltration and apoptosis around hair follicles, inducing hair loss. A well‐known complication of alopecia areata is atopic dermatitis, a typical type 2 inflammatory disease. Hair scientists have shied away from confronting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 79 publications
1
65
0
1
Order By: Relevance
“…IFN-a is a type 1 IFN that is secreted in response to threat signals. 7 Until recently, IFN-c was considered the key cytokine in initiating AA, and the role of IFN-a was restricted to AA induction secondary to viral infection. 30,31 Three studies have revealed the essential role of IFN-a in starting AA, even in the absence of a preceding viral infection, via the enhancement of Th1 immune response surrounding hair bulbs, the stimulation of IFN-c production, the induction of the hair follicle immune privilege collapse, and the initiation of hair bulb apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-a is a type 1 IFN that is secreted in response to threat signals. 7 Until recently, IFN-c was considered the key cytokine in initiating AA, and the role of IFN-a was restricted to AA induction secondary to viral infection. 30,31 Three studies have revealed the essential role of IFN-a in starting AA, even in the absence of a preceding viral infection, via the enhancement of Th1 immune response surrounding hair bulbs, the stimulation of IFN-c production, the induction of the hair follicle immune privilege collapse, and the initiation of hair bulb apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antiviral activity, IFN-a has antitumor and immunomodulatory effects. [5][6][7] The role of IFN-a in noninfectious inflammatory diseases such as systemic lupus erythematosus, lichen planus, and psoriasis has been reported in several studies. [8][9][10] The role of IFN-a in AA has been suggested in reported cases of AA during IFN-a-2b and ribavirin therapy for hepatitis C virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…AA is a chronic autoimmune inflammatory disease characterized by sudden hair loss typically with a course of spontaneous remission and exacerbation [4,5]. The loss of immune privilege is reported as the main trigger of AA [6], but also inflammation and acute or chronic psycho-emotional stress have been reported as causative agents of AA as contributors to its progress [7,8]. Indeed, inflammatory skin diseases, including AA, can be exacerbated by psychological stress via stimulation of the neuroendocrine system [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the 4 JAK2-selective inhibitors in our study had little effect on AA disease reversal. We and others previously showed that IFN-γ plays a critical role in disease induction ( 31 ), whereas in chronic AA, numerous inflammatory cytokines (including IFN-γ) have been implicated in the disease ( 32 ). Additionally, we and others previously showed that both type I and type II IFN (IFN-γ) signaling pathways are active in the alopecia skin both from human patients with AA and C3H/HeJ mice with AA by gene microarray assays ( 33 ).…”
Section: Discussionmentioning
confidence: 99%